Outcome of patients on heart transplant list treated with a continuous-flow left ventricular assist device: Insights from the TRans-Atlantic registry on VAd and TrAnsplant (TRAViATA). (1st February 2021) - Ammirati, Enrico; Brambatti, Michela; Braun, Oscar Ö.; Shah, Palak; Cipriani, Manlio; Bui, Quan M.; Veenis, Jesse; Lee, Euyhyun; Xu, Ronghui; Hong, Kimberly N.; Van de Heyning, Caroline M.; Perna, Enrico; et al.
Abstract: Background: Geographic variations in management and outcomes of individuals supported by continuous-flow left ventricular assist devices (CF-LVAD) between the United States (US) and Europe (EU) is largely unknown. Methods: We created a retrospective, multinational registry of 524 patients who received a CF-LVAD (either HVAD or Heartmate II) between January 2008 and April 2017. Follow up spanned from date of CF-LVAD implant to post-HTx period with a median follow up of 44.8 months. Results: The cohort included 299 (57.1%) EU and 225 (42.9%) US patients. Although the US cohort was significantly older with a higher prevalence of comorbidities, survival was similar between the cohorts (US 63.1%, EU 68.4% at 5 years, unadjusted log-rank test p = 0.43).Multivariate analyses suggested that older age, higher body mass index, elevated creatinine, use of temporary mechanical circulatory support prior CF-LVAD, and implantation of HVAD were associated with increased mortality. Among CF-LVAD patients undergoing HTx, the median time on CF-LVAD support was shorter in the US, meanwhile US donors were younger. Finally, the pattern of adverse events (stroke, gastrointestinal bleedings, late right ventricular failure, and driveline infection) during support differed significantly between US and EU. Conclusions: Although waitlisted patients in the US on CF-LVAD have higher risk comorbid conditions, the overall outcome is similar in US and EU. Geographic variations with regards to donor characteristics, duration of CF-LVAD support prior to transplant, and adverse events on support can explain the disparity in the utilization of mechanical bridge to transplant strategy between US and EU. Highlights: Waitlisted patients in the US on CF-LVAD have higher risk comorbid conditions. Overall outcome of waitlisted patients in the US on CF-LVAD is similar. There are geographic variations with regards to donor characteristics and duration of CF-LVAD support prior to transplant. Older age, use of temporary MCS, implantation of HVAD, higher BMI and creatinine are associated with increased mortality.